2022
DOI: 10.1097/shk.0000000000001920
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-136-5p from Endothelial Progenitor Cells-released Extracellular Vesicles Mediates TXNIP to Promote the Dissolution of Deep Venous Thrombosis

Abstract: Endothelial progenitor cells-released extracellular vesicles (EPCs-EVs) have previously been reported to promote the dissolution of deep venous thrombosis (DVT) through delivery of microRNA (miR). Given that, this research was projected to search the relative action of EPCs-EVs transferring of miR-136-5p in DVT. Methods: From EPCs transfected with miR-136-5p agomir or antagomir, EVs were extracted and then injected into DVTmice. Meanwhile, based on the treatment with EPCs-EVs loading miR-136-5p antagomir, sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…14 Feng et al reported that TXNIP expression was elevated in DVT mice. 15 Our result was similar to their research. However, there is still no clear evidence about TXNIP interact with NLRP3 in DVT formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…14 Feng et al reported that TXNIP expression was elevated in DVT mice. 15 Our result was similar to their research. However, there is still no clear evidence about TXNIP interact with NLRP3 in DVT formation.…”
Section: Discussionsupporting
confidence: 92%
“…13 An increasing number of studies have indicated that TXNIP participated in the formation of thrombosis. 14,15 However, there is no clear evidence presents the change of TXNIP in DVT. In our study, we first investigated the changes of TXNIP and NLRP3 levels at different times after DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the angiogenesis and migration of EPCs are enhanced by miR-126 exosomes [ 94 ], thereby regulating the recanalization of DVT. A recent study has shown that miR-136-5p from EPC-released extracellular vesicles facilitates the dissolution of DVT by inhibiting TXNIP expression, providing a promising treatment target for DVT [ 95 ].…”
Section: Regulatory Effects Of Non-coding Rnas Of Epcs Involved In Ve...mentioning
confidence: 99%
“…The authors concluded that the aberrant expression of circulating miR-424-5p and miR-136-5p was associated with hypercoagulability. At the same time, one of the studies demonstrated the action of endothelial progenitor cell-released extracellular vesicles (EPC-EVs) for transferring miR-136-5p in DVT [81]. It was shown that initially, miR-136-5p expression was suppressed and that the thioredoxin-interacting protein (TXNIP) expression was elevated in DVT mice.…”
Section: In Dvtmentioning
confidence: 99%